TAX REFORMS AND ECONOMIC DEVELOPMENT IN NIGERIA - Nwaiwu, J. N. (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The study investigated the implications of various tax reforms on economic development in Nigeria over the period ranging from 1994 - 2023. The study employed the human development index as a measure of economic development and considered personal income tax, Education tax, company income tax, value-added tax, and petroleum profit tax. Time series data was employed from the yearly report and repository of CBN and FIRS online reports. The employed data analysis techniques in the study are the Stationarity, Autoregressive Distributive Lag, and Granger Causality tests. The study observed mixed stationarity at level and first difference. In the long run, it was observed that only the immediate past value of personal income tax per capita, company income tax per capita, petroleum profit tax income per capita, and education tax income per capita had a valuable influence on economic development. The study therefore concludes that tax revenue has mixed influence on economic development in Nigeria. In light of these findings, the study recommended that; more efficient and effective means and systems for supervision of tax revenue by tax agencies and regulatory bodies should be expedited. Tax agencies should seek means of encouraging taxpayers to pay their taxes to enhance the growth and development of the economic sectors which the taxpayers will also benefit from. Tax holidays and incentives should be expedited to institution, firms, and private individuals who are known to be highly compliant with their tax payments.